From theory to practice: assessing student progress in designing net-zero energy prefabricated buildings - Alshawaf, Bader M M H (My University, 2025)
Energy efficiency is becoming a key part of architectural education, making it important to explore how students engage with related design concepts. This thesis investigates how students’ understanding of energy efficiency concepts developed over a semester-long studio course, participating in the Gateway Decathlon Project competition. The real-world interdisciplinary project involved designing and constructing a prefabricated net-zero energy building, giving students experience in applying energy efficiency strategies and solving real-world challenges in sustainable design. The study applied a longitudinal mixed-method approach to track students' learning progression over the semester. Data were collected through pre- and post-surveys, weekly observations, semi-structured interviews, and tracking building performance outcomes, which include source energy use and daylight analysis. Findings reveal that students developed a stronger understanding of how design decisions affect building performance, applied energy efficiency strategies more effectively, and benefited from interdisciplinary collaboration. Given that the final design was not fully constructed, the project experience still enabled substantial growth in students' ability to design a net-zero energy building. Overall, these findings suggest that hands-on, real-world learning experiences offer an effective approach to developing the knowledge and skills needed for sustainable architectural practice, particularly when aiming to achieve net-zero energy goals.
Keywords: Net-zero energy buildings; Architectural education; Student learning progression; Interdisciplinary collaboration; Modular prefabrication; Hands-on learning; Energy efficiency; Energy simulation tools